General anesthesia for Crisponi syndrome: case report - Chloé Allary; Marco Caruselli; Alexandre Fabre; Frédérique Audic; Fabrice Michel (Brazilian Journal of Anesthesiology, 2020)
Crisponi syndrome is a rare and severe heritable disorder characterised by muscle contractions, trismus, apnea, feeding troubles, and unexplained high fever spikes with multiple organ failure. Here we report perioperative care for endoscopic gastrostomy of a 17 month-old female child with Crisponi syndrome. Temperature in the surgery room was strictly monitored and maintained at 19 °C. The patient was exposed to both inhaled and intravenous anesthetic agents. Surgical and perioperative periods were uneventful. Episodes of fever in Crisponi syndrome arise from CRLF1 mutation, which differs from the physiological pathway underlying malignant hyperthermia. Resumo: A Síndrome de Crisponi é uma condição clínica hereditária grave e rara caracterizada por contrações musculares, trismo, apneia, distúrbios na alimentação, picos de febre alta e inexplicável, e falência de múltiplos órgãos. Descrevemos o cuidado perioperatório de paciente pediátrica com 17 meses de idade, portadora da Síndrome de Crisponi, submetida à gastrostomia endoscópica. A temperatura da sala de cirurgia foi cuidadosamente monitorizada e mantida a 19 °C. A paciente foi submetida a agentes anestésicos inalatórios e venosos. O cuidado cirúrgico e perioperatório desenvolveram-se sem incidentes. As crises de febre na Síndrome de Crisponi originam-se de mutação no gene CRLF1, o que as diferenciam do mecanismo fisiopatológico da hipertermia maligna.